Dysfunction of lipid sensor GPR120 leads to obesity in both mouse and human - Ichimura, Atsuhiko; Hirasawa, Akira; Poulain-Godefroy, Odile; Bonnefond, Amélie; Hara, Takafumi; Yengo, Loïc; Kimura, Ikuo; Leloire, Audrey; Liu, Ning; Iida, Keiko; Choquet, Hélène; Besnard, Philippe; et al. (Nature (London), 2012)
Mice deficient in the lipid sensor GPR120 develop obesity, glucose intolerance and fatty liver when fed a high-fat diet, and a loss-of-function variant in the GPR120 gene strongly contributes to increased obesity in human. A signal for obesity The G-protein-coupled receptor GPR120 is a receptor for free fatty acids, and is involved in homeostasis mechanisms such as fat-cell generation and the regulation of appetite. Here it is shown that without GPR120, mice on a high-fat diet develop obesity, glucose intolerance and fatty liver. In humans, GPR120 expression in adipose tissue is shown to be significantly elevated in obesity. The authors also identify a mutation that inhibits GPR120 signalling activity and is associated with an increased risk for obesity in Europeans. Free fatty acids provide an important energy source as nutrients, and act as signalling molecules in various cellular processes 1 , 2 , 3 , 4 . Several G-protein-coupled receptors have been identified as free-fatty-acid receptors important in physiology as well as in several diseases 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 . GPR120 (also known as O3FAR1) functions as a receptor for unsaturated long-chain free fatty acids and has a critical role in various physiological homeostasis mechanisms such as adipogenesis, regulation of appetite and food preference 5 , 6 , 14 , 15 , 16 . Here we show that GPR120-deficient mice fed a high-fat diet develop obesity, glucose intolerance and fatty liver with decreased adipocyte differentiation and lipogenesis and enhanced hepatic lipogenesis. Insulin resistance in such mice is associated with reduced insulin signalling and enhanced inflammation in adipose tissue. In human, we show that GPR120 expression in adipose tissue is significantly higher in obese individuals than in lean controls. GPR120 exon sequencing in obese subjects reveals a deleterious non-synonymous mutation (p.R270H) that inhibits GPR120 signalling activity. Furthermore, the p.R270H variant increases the risk of obesity in European populations. Overall, this study demonstrates that the lipid sensor GPR120 has a key role in sensing dietary fat and, therefore, in the control of energy balance in both humans and rodents.